Broad Roads in a Thin Country : Infrastructure Concessions in Chile - Gómez-Lobo, Andrés (The World Bank, 2000)
Lessons learned from Chile's highly successful experience in introducing private capital into the transport infrastructure sector. - To increase investment in infrastructure, in the early 1990s Chile's government introduced private capital into the transport infrastructure sector, covering roads and highways, bridges, tunnels, and airports. The chosen mechanism: a concession scheme through which private firms would finance and build a given project and then operate the infrastructure for a set number of years, recovering their investment by collecting tolls from users. Among lessons learned from the experience: · As much as possible, avoid concessioning roads for which there are convenient alternative freeways nearby. · Choose the right variable for awarding a concession. Avoid mechanisms that (by promoting large payments to the state or short-term concession periods) encourage high tolls, and if you choose to award a concession to the firm charging the lowest tolls, place a floor and ceiling on possible bids. The floor is to guarantee the concession's financial viability; the ceiling is to prevent inefficient traffic diversions. Ties at either end should be resolved by a second variable, such as the level of transfers between the state and the firm. · Allow downward toll flexibility so that the concessionaire can react to unexpectedly low traffic flows, especially for certain types of vehicles. · Pay special attention to the tendering mechanism and to the general incentive structure. There are limits to the pure least-present-value-of-revenue (LPVR) auction, but income guarantees do enhance liquidity. In fact, a minimum-income guarantee through an LPVR auction is an instrument for credit enhancement, not income support. Alternatively, some form of financial innovation should be encouraged to make debt service commitments more flexible. · If concessions are te++